Contextualising Maqāṣid al-Sharī’ah and STEM (Science, Technology, Engineering, and Mathematics) education in the era of the Industrial Revolution 4.0 - Ahmad, Abdul Sham; Abd Rahim, Badruel Hairiel; Wan Chik, Wan Yusof; Mohamad, Mohd Hagia Sofia; Mohamad Diah, Nurazzura; Abdul Karim, Abdul Halim (IOP Publishing Ltd., 2020)
The Maqāṣid al-Sharī’ah is one of the disciplines that has been given a unique space in various fields of study nowadays. Though a plethora of studies touched on Maqāṣid alSharī’ah, it rarely linked to the area of STEM education. This phenomenon is crucial in ensuring that the education world is in the mould of the Maqāṣid al-Sharī’ah while at the same time realising the pure will of the Islamic Legal System. STEM Education in the image of the perfect Maqāṣid al-Sharī’ah is believed to be able to shape and produce good people in the future, especially in driving a very challenging industrial revolution. Through a qualitative approach using document analysis, this study attempts to draw out the basics of education by the Maqāṣid al-Sharī’ah that can form the perfect and proper thinking. Subsequently, the investigation continued by discussing the elements of the Maqāṣid al-Sharī’ah identified in these fundamentals. The paper revealed that four main components identified in this issue, namely, the belief in good faith, noble morals, Sharī’ah-based thinking, and professionalising the world. All of these elements acquired by humans through the process of education. The implication is that the study found that placing the STEM education world in the purview of the Maqāṣid al-Sharī’ah should be an influential agenda of national education to drive and meet the challenges of industrial revolution 4.0. Therefore, this effort should be the attention of the national education policymakers who must involve scholars in the field.